1999
DOI: 10.1038/sj.sc.3100785
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical changes in muscle of individuals with spinal cord injury following functional electrical stimulated exercise training

Abstract: Study Design: Longitudinal training. Objectives: To determine the eects of functional electrical stimulated (FES) leg cycle ergometer training on muscle histochemical characteristics in individuals with motor-complete spinal cord injury (SCI). Setting: University of Alberta, Edmonton, Alberta, Canada. Methods: Six individuals with motor-complete SCI (age 31 ± 50 years; 3 ± 25 years postinjury) trained using FES leg cycle ergometry for 30 min, 3 days per week for 8 weeks. Biopsies of the vastus lateralis muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
74
0
11

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 29 publications
4
74
0
11
Order By: Relevance
“…Following SCI, skeletal muscles below the level of an upper motor neuron lesion undergo marked changes in morphological, 14,15 metabolic 43 and contractile properties. 38 Signi®cant changes in skeletal muscle of people with SCI include a pronounced reduction in the proportion of Type I and Type IIa ®bres, 36,37 reduced capillary density, 47 GLUT-4 47,48 contents and an increment in the proportion of Type IIb ®bres. 35,36 Interestingly, muscle ®bre Type proportion, capillarisation, and GLUT-4 content appear to be correlated with insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following SCI, skeletal muscles below the level of an upper motor neuron lesion undergo marked changes in morphological, 14,15 metabolic 43 and contractile properties. 38 Signi®cant changes in skeletal muscle of people with SCI include a pronounced reduction in the proportion of Type I and Type IIa ®bres, 36,37 reduced capillary density, 47 GLUT-4 47,48 contents and an increment in the proportion of Type IIb ®bres. 35,36 Interestingly, muscle ®bre Type proportion, capillarisation, and GLUT-4 content appear to be correlated with insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Research in our facility has also shown that 8 weeks of training (three times/week, 30 min/time) increased ®bre area and capillary number by 23 and 39%, respectively. 38 Increased capillarisation may result in increased delivery of insulin to muscle, which would increase glucose tolerance. One can therefore speculate that changes in muscle characteristics after the ES-assisted training may have improved insulin sensitivity in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In AB subjects, EMSinduced resistance exercise has been shown to result in increases in muscle size and performance (13,14,41). Studies have also shown that the muscles of SCI patients can respond to EMS-mediated contractile activity with some degree of appropriate adaptation, including a modest hypertrophy (11,17,31,36,38,40). However, the absolute changes in mass seen in longterm SCI subjects tend to be relatively small as a result of the atrophied state of the muscle at the start of training (e.g., Refs.…”
mentioning
confidence: 99%
“…However, the absolute changes in mass seen in longterm SCI subjects tend to be relatively small as a result of the atrophied state of the muscle at the start of training (e.g., Refs. 17,31,35,36). For example, Mohr et al (36) reported that EMS cycling evoked a 12% increase in cross-sectional area of the quadriceps femoris muscle in SCI subjects.…”
mentioning
confidence: 99%
“…Stationary FES-induced semireclined leg cycling (FES-LCE) is used clinically as a form of therapeutic exercise to prevent secondary impairments following SCI injury. [1][2][3] Results from these studies indicate that FES-LCE: (1) increases muscle mass, [4][5][6] (2) improves strength and endurance, [7][8][9] (3) facilitates improvements in function, 7 (4) increases cardiovascular fitness, 7,8,10 (5) improves circulation, 7,8,11 (6) decreases swelling due to edema, 12 (7) reduces rate of bone density loss, 13,14 and (8) reduces lower limb blood pooling. 15,16 These results suggest that FES-induced muscle contraction during cycling exercise can be a valuable clinical rehabilitation tool for individuals with SCI in improving rehabilitation outcome, health, and fitness.…”
Section: Introductionmentioning
confidence: 99%